THE INFLUENCE OF OZONE EXPOSURE ON ORGANOLEPTIC AND FLAVONOID LEVELS OF RED BETEL (PIPER CROCATUM RUIZ & PAV.) LEAVES (Jurnal Teknologi (Sciences & Engineering), 2025)
This research aims to determine the levels of flavonoids found in red betel (Piper crocatum Ruiz & Pav.) Leaves and the effectiveness of ozone in reducing cell damage. The ozone was created using a corona discharge ozone generator, which creates an electrical discharge by applying high voltage to ambient air. An ozone analyzer was used to track the ozone concentration to maintain uniformity throughout the tests. Using air and water exposure methods, ozone was applied to red betel leaves (Piper crocatum Ruiz & Pav.) at various durations: 120, 240, 360, and 480 seconds. Organoleptic testing was conducted to detect damage to leaf cells by observing appearance, texture, and aroma changes. The evaporation mechanism was assessed by measuring the balance between the system's internal leaf temperature and the surrounding environment, as indicated by organoleptic changes and mass loss. Measuring flavonoid content using UV-Vis spectrophotometry. Red betel leaf organoleptic data demonstrate that distinct organoleptic are produced by ozone flow and exposure approaches at various times. The exposure method through water produced the greatest organoleptic results with an ozone flow time of 240 seconds. The amounts of flavonoids in red betel leaves showed variations in ozone concentration and exposure method. The maximum concentrations of red betel leaf flavonoids (48.69 + 0.48 mg QE/g) were detected at an ozone flow time of 240 seconds using the exposure method through water. Significant differences (p < 0.05) in flavonoid levels and organoleptic qualities were found in a one-way ANOVA.